Scheduling with the Probabilistic Coupling Method II (PTCM II) – assuming continuity of work on the working sectors - Paulina Kostrzewa-Demczuk; Magdalena Rogalska (Archives of Civil Engineering)
Effective planning is crucial in the construction sector to ensure projects are completed on time and on budget. However, the construction industry faces various challenges that can complicate the planning process. There are often delays, exceedances of the baseline and increases in investment costs. One planning method is Time Couplings Methods (TCM), which can be improved using predictive multivariate statistical model method (MMSM) construction process times and standard deviations. A new scheduling method in the probabilistic approach was developed – Probabilistic Time Couplings Method II (PTCM II). In PTCM II, the priority is to maintain the continuity of work on working sectors, because sector downtime is unfavorable and extends the investment implementation time. The work presents a case study and compares it with other planning methods and with the real time of the considered investment. he results clearly indicate that the developed methodology is correct, provides good mapping and can be successfully used in planning construction works.